The Implementation of Genre Based Approach in Teaching Recount Text to Promote Students' Writing Skill - Lail, Iftitahul (RETAIN, 2022)
The aims of this research are to know how Genre Based approach is implemented, Genre Based Approach can promote students’ writing competence or not and to know their responses towards it. The researcher designed this research using quantitative method and qualitative method. Quantitative method was used to know students’ improvement in writing and qualitative method was used to know how GBA was implemented and students’ response towards it. Subjects of this research were 1st grade students of senior high school. There were 25 participants who actively participated in this research. The data were collected by conducting tests (pre and post-test), doing observation and giving questionnaire. The data were analyzed using SPSS to make it easier to find the result. The first result of this research was that Genre Based Approach was implemented well. All stages were implemented from BKOF (Building Knowledge of Field), MOT (Modelling of the Text), JCOT (Join Construction of the Text) and ICOT (Independent Construction of the Text). Secondly, the implementation of GBA could promote students’ writing competence because the ρ (two-tailed) showed .000 which was less than 0.05. It means that there was significant effect of GBA towards students’ writing. Last, some students were helped with this method especially in understanding a text. Some of them also were helped in different aspects such as understanding the social function, structure of the text, language features and etc. Keywords: implementation, writing, genre-based approach.